Vouchers versus Lotteries: What Works Best in Promoting Chlamydia Screening? A Cluster Randomized Controlled Trial. (26th November 2013) - Niza, Claudia; Rudisill, Caroline; Dolan, Paul
Abstract: In this cluster randomized trial (N = 1060), we tested the impact of financial incentives (£5 voucher vs. £200 lottery) framed as a gain or loss to promote Chlamydia screening in students aged 18–24 years, mimicking the standard outreach approach to student in halls of residence. Compared to the control group (1.5%), the lottery increased screening to 2.8% and the voucher increased screening to 22.8%. Incentives framed as gains were marginally more effective (10.5%) than loss‐framed incentives (7.1%). This work contributes to the literature by testing the predictive validity of Prospect Theory to change health behavior in the field.